Clinical impact of adjuvant radiation therapy delay after neoadjuvant chemotherapy in locally advanced breast cancer. (April 2018) - Silva, Saulo Brito; Pereira, Allan Andresson Lima; Marta, Gustavo Nader; de Barros Lima, Kennya Medeiros Lopes; de Freitas, Thiago Brasileiro; Matutino, Adriana Reis Brandão; de Azevedo Souza, Manoel Carlos Leonardi; de Azevedo, Renata Gondim Meira Velame; de Viveiros, Pedro Antonio Hermida; da Silva Lima, Julianne Maria; Filassi, José Roberto; de Andrade Carvalho, Heloísa; et al.
Abstract: Background: and Purpose: Post-operative radiation therapy (PORT) is usually indicated for patients with breast cancer (BC) after neoadjuvant chemotherapy (NAC) and surgery. However, the optimal timing to initiation of PORT is currently unknown. Material and methods: We retrospectively evaluated data from patients with BC who received PORT after NAC and surgery at our institution from 2008 to 2014. Patients were categorized into three groups according to the time between surgery and PORT: <8 weeks, 8–16 weeks and >16 weeks. Results: A total of 581 patients were included; 74% had clinical stage III. Forty-three patients started PORT within 8 weeks, 354 between 8 and 16 weeks and 184 beyond 16 weeks from surgery. With a median follow-up of 32 months, initiation of PORT up to 8 weeks after surgery was associated with better disease-free survival (DFS) (<8 weeks versus 8–16 weeks: HR 0.33; 95% CI 0.13–0.81; p = 0.02; <8 weeks versus >16 weeks: HR 0.38; 95% CI 0.15–0.96; p = 0.04) and better overall survival (OS) (<8 weeks versus 8–16 weeks: HR 0.22; 95% CI 0.05–0.90; p = 0.036; <8 weeks versus >16 weeks: HR 0.28; 95% CI 0.07–1.15; p = 0.08). Conclusion: PORT started up to 8 weeks after surgery was associated with better DFS and OS in locally-advanced BC patients submitted to NAC. Our findings suggest that early initiation of PORT is critically important for these patients. However, the low numbers of patients and events in this study prevent us from drawing firm conclusions. Highlights: Timing of PORT in patients breast cancer treated with neoadjuvant chemotherapy may play an important role. From this specific patient group, initiation of RT within 8 weeks of surgery may be associated with better survival. Larger studies needs to be done to confirm whether starting postoperative RT before 8 weeks positively influences survival.